Assessing the preceptorship model in clinical teaching of undergraduate nursing and midwifery students in Malawi - Mhango, Lucky (University of Malawi, Kamuzu College of Nursing, 2021)
Preceptorship is one of the models applied in clinical teaching where nursing educational institutions rely on registered nurses (RNs) trained as preceptors to take the role of clinical instructors. Malawi adopted the preceptorship model in response to a critical shortage of human resources. This study, therefore, aimed at assessing the preceptorship model in clinical teaching of undergraduate nursing and midwifery students in Malawi. This explanatory sequential mixed methods study was conducted at four public tertiary hospitals; a mental hospital, Christian Health Association of Malawi (CHAM) hospital and five district hospitals. A total of 87 preceptors completed a Clinical Preceptor Experience Evaluation Tool (CPEET) and 12 participated in face-to-face individual interviews. Quantitative data were analysed through descriptive statistics while qualitative data were analysed by thematic content analysis. Results revealed that a preceptorship model is an effective approach to clinical teaching with benefits to both the students and preceptors. Post hoc comparisons using the Tukey HSD test indicated that the role domain mean scores for the respondents with 4-5 years of post-registration experience (M = 6.61, SD = 0.36) was significantly different (p=0.02) than those with >9 years (M = 6.13, SD = 0.60). These results showed that respondents with 4-5 years of experience were more confident than those with >9 years of experience. The study revealed some constraints in the implementation of the preceptorship model and the main challenges included the high preceptor-to-student ratio due to staff shortages, lack of resources and poor collaboration with faculty members. These factors compromised the effectiveness of the preceptorship model in facilitating student learning.